The Influence of Malay Culture in Inheritance Distribution in Malaysia: (Pengaruh Budaya Melayu dalam Gelagat Pembahagian Harta Pusaka di Malaysia) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
The Malays have specific practices normally termed as "Malay culture", "Malay behaviour" or "Malay customs". One element related to such practices is the distribution of inheritance. Influences from these customary practices do not merely affect the method of distribution but also the trend in managing the distribution as well. In practice, this influence supersedes laws as ordained by religion. One example is an estate that is divided equally among brothers and sisters. Normally, apportionment of an estate is not executed until a couple is deceased. This hybrid practice shows there is cultural assimilation in religious practices. Such practices have seeped into the community, so much so that some members of the community are no longer able to differentiate between culture and religion. As such, this research aims to expose the fusion of custom and common practice, as well as its impact on the culture of the Malays in Malaysia. The observation focused on a comparative method between Islamic law and customary practice, especially in the distribution of inheritance. The findings present the cultural practices of the Malays with regard to custom and religion in Malaysia, and outlines steps to be taken to ensure such assimilated practices are in line with Islamic law.Keywords: Malay, custom, inheritance, attitude, Islamic law